THE INFLUENCE OF ETHNOMATICS IN SIPIROK WOVEN FABRIC PATTERNS ON STUDENTS' CREATIVITY ABILITIES IN GRADE VII - Yusminah; Nurdalilah; Adek Nilasari Harahap (Journal Education Innovation (JEI), 2025)
This study aims to determine the effect of ethnomathematics using Sipirok woven fabric patterns on students' creativity skills in the plane geometry material for Grade VII-2. This research adopts an experimental method with the goal of enhancing students' creativity through the integration of ethnomathematics using Sipirok woven fabric patterns. The sample of this study consisted of 40 students from classes VII-1 and VII-2. The pre-test results revealed that the control class achieved an average score of 59.9, while the experimental class obtained an average score of 58.2. After the implementation of the experimental treatment, the post-test results showed an improvement in creativity skills, with the experimental class achieving an average score of 78.35 and the control class achieving 72.5. The average score of 78.35 falls into the “moderate” category for students' creativity skills. According to the criteria, a class is considered to have achieved creativity skills if it has reached at least the “moderate” category. Based on the comparison of the pre-test and post-test results, there was an increase in students' creativity skills in the experimental class, rising from an average of 58.2 to 78.35. The hypothesis test results showed a significance value of 8.13 > 2.024, indicating that the use of ethnomathematics with Sipirok woven fabric patterns has a significant effect on the creativity skills of Grade VII students. Furthermore, the Sipirok woven fabric patterns can be associated with mathematical concepts, particularly in the study of plane geometry. This connection was supported by interview findings from a Sipirok woven fabric artisan.